2013
DOI: 10.3762/bjoc.9.93
|View full text |Cite
|
Sign up to set email alerts
|

Gold-catalyzed oxycyclization of allenic carbamates: expeditious synthesis of 1,3-oxazin-2-ones

Abstract: SummaryA combined experimental and computational study on regioselective gold-catalyzed synthetic routes to 1,3-oxazinan-2-ones (kinetically controlled products) and 1,3-oxazin-2-one derivatives (thermodynamically favored) from easily accessible allenic carbamates has been carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…In this study, Ag NPs architectured COF permits the cyclization reactions of 3d,e into 4d,e (alkylidene-oxazinones). Although a significant advancement of the reaction was observed, this is evident that such challenging products have been generated in this method . Moreover, cyclization at the 5-endo position (cyclo-hydroamination) is usually a competitive method over 6-exo cyclization (carboxylative cyclization process).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, Ag NPs architectured COF permits the cyclization reactions of 3d,e into 4d,e (alkylidene-oxazinones). Although a significant advancement of the reaction was observed, this is evident that such challenging products have been generated in this method . Moreover, cyclization at the 5-endo position (cyclo-hydroamination) is usually a competitive method over 6-exo cyclization (carboxylative cyclization process).…”
Section: Resultsmentioning
confidence: 99%
“…In order to prepare a library of new imidazo[1,2- c ][1,3]oxazin-5-one heterocycles, N -Boc-4-bromo-5-methyl-2-phenylethynylimidazole 1a was studied as a model substrate and subjected to some annulation process conditions which have been already described in the literature. 25,37,46,49,50,57–64 Compound 1a , which is a suitable substrate for undergoing intramolecular annulation, was prepared following our recent procedure involving the regioselective Sonogashira cross coupling reaction of N -Boc-2,5-dibromo-4-methylimidazole. 48 Initially, the zinc catalyst (ZnCl 2 ) was used in dichloromethane at 40 °C but it was found to be totally inert since the starting material was completely recovered after 48 h (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…We then attempted to protect the hydroxyl group, but found that the resultant allene 29 underwent Au‐mediated cyclization to produce cyclic carbamate 30 . This undesired product probably results from the attack of the carbamate to allene through the oxygen rather than the nitrogen atom . To fix this problem, we decided to let the free amine attack the allene moiety.…”
Section: Figurementioning
confidence: 99%